Topsoil structure stability in a restored floodplain: Impacts of fluctuating water levels, soil parameters and ecosystem engineers - Schomburg, Andreas Cédric; Schilling, Oliver; Guenat, Claire; Schrimer, Mario; Le Bayon, Renée-Claire; Brunner, Philip (My University, 2018)
Ecosystem services provided by floodplains are strongly controlled by the structural stability of soils. The development of a stable structure in floodplain soils is affected by a complex and poorly understood interplay of hydrological, physico-chemical and biological processes. This paper aims at analysing relations between fluctuating groundwater levels, soil physico-chemical and biological parameters on soil structure stability in a restored floodplain.Water level fluctuations in the soil are modelled using a numerical surface-water–groundwater flow model and correlated to soil physico-chemical parameters and abundances of plants and earthworms. Causal relations andmultiple interactions between the investigated parameters are tested through structural equation modelling (SEM). Fluctuatingwater levels in the soil did not directly affect the topsoil structure stability, but indirectly through affecting plant roots and soil parameters that in turn determine topsoil structure stability. These relations remain significant for mean annual days of complete and partial (N25%)water saturation. Ecosystemfunctioning of a restored floodplainmight already be affected by the fluctuation of groundwater levels alone, and not only through complete flooding by surface water during a flood period. Surprisingly, abundances of earthworms did not showany relation to other variables in the SEM. These findings emphasise that earthworms have efficiently adapted to periodic stress and harsh environmental conditions. Variability of the topsoil structure stability is thus stronger driven by the influence of fluctuatingwater levels on plants than by the abundance of earthworms. This knowledge about the functional network of soil engineering organisms, soil parameters and fluctuating water levels and how they affect soil structural stability is of fundamental importance to define management strategies of near-natural or restored floodplains in the future